Implementation of Welding Production Unit Learning Model for Students’ Entrepreneurial Preparedness of Public Vocational High School - Susilo, Ferry Cahyo; Widiyanti, Widiyanti; Isnandar, Isnandar (Fakultas Teknik Universitas Negeri Malang, 2022)
Vocational High Schools are expected to produce graduates able to create job vacancies and produce competitive job seekers. For this purpose, they need a special curriculum. One of the applicable learning methods relevant to the need is the creation of production units. By having practical experience in a business unit, vocational students are expected to have a motivation to make entrepreneurial endeavors so that vocational graduates are able to work professionally in the industrial world and work independently as entrepreneurs. This research was a descriptive using the qualitative approach. The data were collected by holding interviews to describe the effectiveness of the production unit of a welding workshop in indicating the entrepreneurial preparedness of the students of Public Vocational High School (PVHS) 2 Tulungagung. The research result showed that the implementation of the learning model for welding production unit affected students’ interest in entrepreneurship and preparedness for it. As many as 55.88 percent of respondents expressed their readiness for entrepreneurship after graduation. However, the welding production unit of PVHS 2 Tulungagung still needed evaluation and improvement especially in their marketing, students’ involvement and the management of financial administration